On equivalence categories of microbundles - Matuzevičius, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Матузявичюс. Об эквивалентности категорий микропучков A. Matuzevičius. Apie mikroišsluoksniavimų kategorijų ekvivalentiškumą